2010
DOI: 10.1027/1618-3169/a000036
|View full text |Cite
|
Sign up to set email alerts
|

Is the Future the Right Time?

Abstract: Spanish and English speakers tend to conceptualize time as running from left to right along a mental line. Previous research suggests that this representational strategy arises from the participants' exposure to a left-to-right writing system. However, direct evidence supporting this assertion suffers from several limitations and relies only on the visual modality. This study subjected to a direct test the reading hypothesis using an auditory task. Participants from two groups (Spanish and Hebrew) differing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
171
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(190 citation statements)
references
References 39 publications
14
171
1
Order By: Relevance
“…This result is in line with the facilitation of timespace congruent responses by auditorily presented words reported by Ouellet et al (2010b). Most importantly, however, the words employed in the present study have the ability to prime the mental time-line.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in line with the facilitation of timespace congruent responses by auditorily presented words reported by Ouellet et al (2010b). Most importantly, however, the words employed in the present study have the ability to prime the mental time-line.…”
Section: Resultssupporting
confidence: 91%
“…Whereas some studies reported a time-space congruency effect evoked by auditory words (Kong and You 2012;Lakens et al 2011; see also Ishihara et al 2008 for a spatio-temporal compatibility effect with non-word auditory stimuli), Ouellet et al (2010b) did not find an interaction between the left and right stimulus location and the past and future references. Since such an interaction had been repeatedly demonstrated for visual stimuli (e.g., Santiago et al 2007;Torralbo et al 2006), Ouellet et al (2010b) provides some indication of the involvement of modalityspecific processes in the activation of the mental time-line. Recently, Santiago et al (2011) proposed a working memory based theory which captures the influence of task demands and modality-specific processes on the activation of spatial codes by temporal codes.…”
Section: Introductionmentioning
confidence: 87%
“…The use of an external FoR for representing temporal order is consistent with the hypothesis that the direction of the MTL depends on orthographic experience (Casasanto & Bottini, 2014;Fuhrman & Boroditsky, 2010;Ouellet et al, 2010). Reading text from left to right, whether with the eyes or the hands, leads to a similar horizontal representation of temporal order in which earlier times are located to the left of later times, independent of the position of one's hands.…”
Section: Discussionsupporting
confidence: 76%
“…The experience of reading and writing seems to play a role in establishing the direction and orientation of the MTL (Casasanto & Bottini, 2014;Fuhrman & Boroditsky, 2010;Ouellet, Santiago, Israeli & Gabay, 2010;Tversky, Kugelmass & Winter, 1991). Events unfold rightward along the MTL in people who habitually read from left to right, and leftward in people who read from right to left (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation